Micro- and nano-plastics induce inflammation and cell death in human cells - Bishop, Brandon; Webber, William S.; Atif, Shaikh M.; Ley, Ashley; Pankratz, Karl A.; Kostelecky, Rachael; Colgan, Sean P.; Dinarello, Charles A.; Zhang, Wei; Li, Suzhao (Frontiers in Immunology, 2025)
IntroductionThe presence of micro- and nano-plastics (MNPLs) in the environment has increased significantly in the past decades. However, the direct impact of MNPL particles on human health remains unclear.MethodsIn this study, we utilized a modified extraction method with a previously reported staining technique to develop a novel approach for identifying individual plastics in mixtures of MNPLs of commercial and environmental origins to be able to investigate their impacts on human cell inflammation and cell death. Polypropylene (PP), polyethylene (PE), polystyrene (PS), and polyethylene terephthalate (PET) were the plastics analyzed. The plastic composition of the environmental MNPLs was characterized using multiple analytical techniques, including Fourier transform infrared spectroscopy, confocal imaging, scanning electron microscopy, and X-ray diffraction.ResultsWe found that both commercial and environmental MNPLs, especially PET, impose a strong inflammatory response on various human cells and tissues. At 1 mg/mL, they robustly stimulate inflammatory IL-1β and IL-6 secretion in a time-dependent manner. Importantly, we observed that the MNPLs induced variable inflammatory responses in cells depending on their plastic composition. Environmental samples rich in PET showed a strong dose-dependent response and induced IL-1β secretion at doses as low as 100 ng/mL. In addition, MNPLs can induce human cell death with or without obviously altering the cell morphology.DiscussionThese findings are significant because they represent the first instance of authentic MNPLs being collected from ecological water samples for characterization and the first time the direct influences of commercial and environmental MNPLs have been compared in human cell studies. The methods developed in this study provide a foundation for future research to isolate MNPLs from the environment and explore their potential impacts on human health and disease development.